Faktor – Faktor yang Mempengaruhi Tingkat Kecemasan Ibu Hamil pada Masa Pandemi Covid 19 - Andi Ulfa Fatmasanti; Kiki Reski Rahmadani Bakri; Asrianti Safitri Muchtar (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2022)
The COVID-19 pandemic is a disease that is troubling the whole world, this disease attacks the respiratory tract and in all age groups including pregnant women. Pregnant women are very vulnerable to psychological disorders, namely anxiety. Psychological problems in pregnancy are often associated with adverse effects on the mother and fetus as well as on child development. The purpose of this study was to determine the factors that affect the level of anxiety in pregnant women during the covid-19 pandemic at the Mamajang Health Center in March-July 2020. This study was conducted using a cross-sectional approach with a sample of 30 pregnant women and instruments. in this study is a questionnaire on the anxiety scale HARS (Hamilton Anxiety Rating Scale). The results of the Chi-Square test analysis showed that there was a relationship between age and anxiety with a p value of 0.000 < (0.05), there was a relationship between education and anxiety with a p value of 0.019 < (0.05), there was a relationship between work and anxiety with a p value of 0.034 < (0.05), there is a relationship between parity and anxiety with a p value of 0.000 < (0.05). Keywords: Factor, Anxiety, Pregnant Women, Covid-19